2018
DOI: 10.1139/facets-2018-0015
|View full text |Cite
|
Sign up to set email alerts
|

Shining light on recent advances in microbial mercury cycling

Abstract: Mercury (Hg) is a global pollutant emitted primarily as gaseous Hg0 that is deposited in aquatic and terrestrial ecosystems following its oxidation to HgII. From that point, microbes play a key role in determining Hg’s fate in the environment by participating in sequestration, oxidation, reduction, and methylation reactions. A wide diversity of chemotrophic and phototrophic microbes occupying oxic and anoxic habitats are known to participate directly in Hg cycling. Over the last few years, new findings have co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 122 publications
1
34
3
Order By: Relevance
“…Recent reviews critically summarized Hg II uptake and MMHg efflux in methylating anaerobes, methods and equations to analyze Hg methylation rates (Regnell and Watras ) as well as chemotrophic and biotic Hg methylation and demethylation processes by anaerobes and phototrophs (Grégoire and Poulain ; Du et al ). In this review, we aim to summarize the main findings on mechanisms responsible for the formation of MMHg, focusing in detail on the new knowledge recently gained on microorganisms involved in MMHg formation.…”
Section: The Mercury Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reviews critically summarized Hg II uptake and MMHg efflux in methylating anaerobes, methods and equations to analyze Hg methylation rates (Regnell and Watras ) as well as chemotrophic and biotic Hg methylation and demethylation processes by anaerobes and phototrophs (Grégoire and Poulain ; Du et al ). In this review, we aim to summarize the main findings on mechanisms responsible for the formation of MMHg, focusing in detail on the new knowledge recently gained on microorganisms involved in MMHg formation.…”
Section: The Mercury Problemmentioning
confidence: 99%
“…Also, an increase in nutrients, associated to an enhanced algae biomass production, increased MMHg formation in sediments (Bravo et al ; Herrero Ortega et al ). Changes in redox conditions might also affect iron, sulfur and Hg II speciation (Liem‐Nguyen et al ), and the activity of the microorganisms (Grégoire and Poulain ) and consequently Hg II methylation (Fig. , orange boxes and arrows).…”
Section: Physico‐chemistry Plays a Pivotal Role In Hgii Methylationmentioning
confidence: 99%
“…In our commonly held conceptual cycle, Hg settles to the anoxic zones of lakes as less bioavailable Hg-DOM or Hg-particle complexes after deposition from the atmosphere as more bioavailable HgII (Chiasson-Gould et al, 2014). In a revised model (Figure 1), redox reactions can "reset" Hg speciation far from the air/water interface results in the incorporation of an additional source of fresh bioavailable Hg (Hg0, or its oxidation products) for methylation (Chiasson-Gould et al, 2014;Grégoire and Poulain, 2018). Under anoxic conditions, HgII reduction can occur through abiotic reactions with DOM (Gu et al, 2011) and iron-bearing minerals (Bone et al, 2014;Wiatrowski et al, 2009), but anaerobic microbes can also participate directly (Lin et al, 2014;Liu and Wiatrowski, 2018;Lu et al, 2016;Schaefer et al, 2002;Wiatrowski et al, 2006;Zhao et al, 2017).…”
Section: Current View Of the Mercury Cycling In Freshwater Lakes And mentioning
confidence: 99%
“…Under anoxic conditions, HgII reduction can occur through abiotic reactions with DOM (Gu et al, 2011) and iron-bearing minerals (Bone et al, 2014;Wiatrowski et al, 2009), but anaerobic microbes can also participate directly (Lin et al, 2014;Liu and Wiatrowski, 2018;Lu et al, 2016;Schaefer et al, 2002;Wiatrowski et al, 2006;Zhao et al, 2017). The well-known mer operon (genes encoding for Hg detoxification via reduction) is generally absent in obligate anaerobes (Barkay et al, 2010) and phototrophs (Grégoire and Poulain, 2018) suggesting that alternate yet unknown pathways exist to explain their ability to produce Hg0. Recent work found no evidence of Hg0 aq abundance directly limiting Hg methylation (Poulin et al, 2019) , and although at face value the findings could be seen as contradicting prior work, it is equally likely that Hg undergoes active redox cycles under anoxic conditions which may not necessarily result in the net accumulation of detectable levels of Hg0 aq .…”
Section: Current View Of the Mercury Cycling In Freshwater Lakes And mentioning
confidence: 99%
“…In contrast to mer-mediated Hg reduction and demethylation, dedicated genetic determinants have yet to be identified for anaerobic Hg reduction, making these pathways challenging to study from a mechanistic standpoint. Furthermore, while some studies have shown that Hg 0 can significantly contribute to Hg speciation in anoxic habitats (27,28), it is 5 possible that low levels of Hg 0 are maintained by an active cycle of reduction and oxidation (29).…”
Section: Introductionmentioning
confidence: 99%